Early Childhood Education In Islamic Education Perspective - Imam Tabroni; Jamali Sahrodi; Ulfiah; Lindawati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
To find out how the involvement of Islamic education experts in studying early childhood education, it is deemed necessary to conduct a study entitled "Early Childhood Education in the Perspective of Islamic Education". This study aims to analyze various aspects of early childhood education, especially in the approach or study of Islamic education, as well as to find out the concept of early childhood education in the perspective of Islamic education, especially with regard to the basis and objectives, curriculum/materials, educational methods and its evaluation. This study uses a non-interactive qualitative method, namely research on concepts through a document analysis. The non-interactive qualitative research approach chosen in conducting this study/research is an analytical concept. This research is focused on analyzing several research objects, in the form of books or books related to early childhood education and Islamic education. The research data were analyzed using content analysis techniques.